“I’m Told I Don’t Look Like a Foreigner”: Everyday Racism in Contemporary Italy - Quassoli, Fabio (2023)
In our article, we aim to explore the experience of everyday racism of young people with migrant parents in Italy. Drawing on the analysis of 20 interviews, we seek to reconstruct the overall dynamics of racial microaggressions, highlighting how the context in which microaggressions occur and the interplay between ethnic background, gender, and somatic features influences the interpretations and reactions of the victims. We highlight the boundary work and identity negotiation process carried out in everyday encounters. We also show that participants’ experience oscillates between the claim of not-taken‐for‐granted citizenship, the feeling of being confined within ethno‐cultural imaginaries, and the experience of overt manifestations of racism. Finally, we highlight both the process by which victims come to recognise racial microaggressions and the obstacles they face in coping with them.